Perfil epidemiológico e biologia tumoral do câncer de mama em mulheres da Região Norte do Brasil - Franca, Daniele Carvalhais (2023)
INTRODUCTION: Retrospective cohort to describe the epidemiological data of women with breast cancer at a referral center in oncology in the North region of Brazil between January 2012 and December 2021. RESULTS: 420 patients were included, most of them female (99.5%), with complete elementary school (33.3%) and brown (68%). The mean age at diagnosis was 49 years. Most patients are from Rondônia (87.8%). Forty-five percent were born in the North region and 55% in other regions of Brazil. Eighty percent of injuries were classified as CDI. Regarding molecular subtypes, 32.7% were luminal A, 25.1% luminal B, 19.4% HER2 overexpressed and 12.8% triple negative. 76.8% of patients received chemotherapy; radiotherapy, 81.5%; 91.2% underwent surgery; 71.8% received hormone therapy and 21.2% targeted therapy. When the patients were subdivided by age £40 years and > 40 years, there was a statistically significant difference in the association with staging (p=0.000), histological type (p= 0.035), molecular subtype (p=0.000), neoadjuvant chemotherapy (p=0.000). = 0.005) and genetic counseling (p=0.001). There was a statistically significant correlation with color/race (p= 0.012), staging (p= 0.005), family history of any type of cancer (p= 0.040), molecular subtype (p= 0.001), neoadjuvant chemotherapy (p=0.000) and radiotherapy (p= 0.000). The median survival was 7.99 years. The 5-year overall survival was 81%. Survival in relation to staging was lower the higher the stage. Twenty-four distinct variants were described in patients undergoing genetic testing, 16 of uncertain significance (VUS) and 8 pathogenic. Three new variants have been described: ATM (c.8726G>C), BRCA2 (c.2232A>C) and ERCC5 (c.2164G>Ap). CONCLUSION: In this study, the age at diagnosis of breast cancer was lower, the tumors are of a more aggressive subtype and patients are admitted in more advanced stages. Approximately 46% of patients did not start treatment within the established period. This rate is better compared to national data in which 50.9% of women are in this situation. Survival is lower compared to national and international data. Despite the small number of patients referred for genetic testing, it is important to search for germline mutations in this population.